Tuscarora Lake, Johnson County - Morris, Colin (Kansas State University, The Chapman Center for Rural Studies, 2016)
It is not exactly clear what became of the forgotten settlement known as Tuscarora Lake; however, clues from the town’s past can be examined to better expose the reality behind Tuscarora Lake’s demise. The ending of Tuscarora Lake was directly linked to national events, beginning with the border ruffian William C. Quantrill, the Border Wars between Kansas and Missouri, as well as the Civil War. This study uses old maps, field work, a personal diary, and newspaper articles to reconstruct this history.
Colin Morris, “Tuscarora Lake, Johnson County,” Chapman Center Research Collections, https://ccrsresearchcollections.omeka.net/items/show/186.
Keywords: Tuscarora Lake; Shawnee; BNSF Railway; Johnson County; William C. Quantrill; Santa Fe Trail